Sosialisasi Dampak dan Pencegahan Kekerasan dalam Rumah Tangga Pada Anggota “Lembaga Pembinaan Pengembangan Keluarga Sakinah” Badan Komunikasi Pemuda Remaja Masjid Indonesia Nusa Tenggar Barat - Lenny Herlina; Arfi Syamsun; Ida Lestari Harahap; Pujiarohman (Insan Kreasi Media, 2022)
Abstract: The aim of this community service is to provide a deep understanding of the impact and prevention of household violence for members of Lembaga Pembinaan Pengembangan Keluarga Sakinah, Youth Communication Agency for Indonesian Mosque, West Nusa Tenggara. The method applied in this community service is in the form of socialization related to increasing understanding of the impact and how to prevent domestic violence. This socialization is considered important considering the confusion that generally occurs among Muslim women and men who tend to misunderstand several things regarding domestic violence in the perspective of religion and social life. This activity took place in two sessions, namely an educational session related to domestic violence in the perspective of Islam and law, as well as an educational session related to psychological, social and economic impacts.. This education packaged in the form of socialization is expected to lead to increased awareness of the importance of preventing domestic violence and what steps to take if experiencing or knowing of a case of domestic violence. This activity produces an output in the form of articles, so that information regarding the prevention of domestic violence is not only limited to LPPKS or majlis taklim groups but can be absorbed by the wider community.